A moment recursive formula for a class of distributions - Rincón, Luis (2021)
We provide a recursive formula for the computation of moments of distributions belonging to a subclass of the exponential family. This subclass includes important cases as the binomial, negative binomial, Poisson, gamma and normal distribution, among others. The recursive formula provides a procedure to sequentially calculate the moments using only elementary operations. The approach makes no use of the moment generating function.